Prenatal Detection of Congenital Duodenal Obstruction-Impact on Postnatal Care - Kerstin Saalabian; Florian Friedmacher; Till-Martin Theilen; Daniel Keese; Udo Rolle; Stefan Gfroerer (MDPI AG, 2022)
Background: Duodenal obstruction is a rare cause of congenital bowel obstruction. Prenatal ultrasound could be suggestive of duodenal atresia if polyhydramnios and the double bubble sign are visible. Prenatal diagnosis should prompt respective prenatal care, including surgery. The aim of this study was to investigate the rate and importance of prenatally diagnosed duodenal obstruction, comparing incomplete and complete duodenal obstruction. Methods: A retrospective, single-center study was performed using data from patients operated on for duodenal obstruction between 2004 and 2019. Prenatal ultrasound findings were obtained from maternal logbooks and directly from the investigating obstetricians. Postnatal data were obtained from electronic charts, including imaging, operative notes and follow-up. Results: A total of 33/64 parents of respective patients agreed to provide information on prenatal diagnostics. In total, 11/15 patients with complete duodenal obstruction and 0/18 patients with incomplete duodenal obstruction showed typical prenatal features. Prenatal diagnosis prompted immediate surgical treatment after birth. Conclusion: Prenatal diagnosis of congenital duodenal obstruction is only achievable in cases of complete congenital duodenal obstruction by sonographic detection of the pathognomonic double bubble sign. Patients with incomplete duodenal obstruction showed no sign of duodenal obstruction on prenatal scans and thus were diagnosed and treated later.